2011
DOI: 10.1111/j.1399-0039.2011.01770.x
|View full text |Cite
|
Sign up to set email alerts
|

On the future of HLA

Abstract: As the immunobiological function of the HLA (human leucocyte antigen) class I and II molecules was revealed, we have seen an explosive development of the HLA field. Today, the HLA complex occupies a central position in basic and clinical immunology. In this Opinion article, I will briefly discuss some challenges which in my opinion are more important than others in the near future of HLA, with a focus on products of the classical HLA class I and II genes. Matching for HLA antigens will continue to be of import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
(95 reference statements)
2
8
0
Order By: Relevance
“…to stimulate B lymphocyte transform into IgE secreting plasma cells, accompanied with a decrease in Th1 type cytokines (IFN-γ, IL-2, IL-12). 6,[25][26][27] In our study, we confirmed that, accompanied with the AR symptoms, OVA induced a Thl/Th2 imbalance and led to a Th2 dominant immune response with increased cytokine IL-4 levels, and a decrease of IFN-γ and IL-2 ( Figure 2). The differentiation of naive T-helper (Th) cells towards Th2 or Th1 is decided by the transcription factors GATA-3/Tbet.…”
Section: Discussionsupporting
confidence: 77%
“…to stimulate B lymphocyte transform into IgE secreting plasma cells, accompanied with a decrease in Th1 type cytokines (IFN-γ, IL-2, IL-12). 6,[25][26][27] In our study, we confirmed that, accompanied with the AR symptoms, OVA induced a Thl/Th2 imbalance and led to a Th2 dominant immune response with increased cytokine IL-4 levels, and a decrease of IFN-γ and IL-2 ( Figure 2). The differentiation of naive T-helper (Th) cells towards Th2 or Th1 is decided by the transcription factors GATA-3/Tbet.…”
Section: Discussionsupporting
confidence: 77%
“…HLA class I and class II genes map on the short arm of the chromosome 6 (6p21.3) and code for cell surface glycoproteins important in the antigen presentation and self-recognition by immune cells [32,33]. HLA class I heterodimers are constituted by an alpha-heavy chain, encoded by HLA-A , B or C loci, and by a small beta2-microglobulin molecule whose gene maps on chromosome 15.…”
Section: Reviewmentioning
confidence: 99%
“…Many autoimmune diseases are reported to be associated with specific HLA-class II alleles [35]. Auto-reactive processes that involve the activation of cytokine producing T-cells may occur during infection.…”
Section: Discussionmentioning
confidence: 99%